Myxedema ascites with elevated serum CA 125 concentration - Duarte, D. R.; Chang, C. V.; Minicucci, Marcos Ferreira [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; Inoue, RMT; Matsui, M.; Okoshi, Marina Politi [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Paiva, SAR (Lippincott Williams & Wilkins, 2006)
We report a case of myxedema ascites and markedly elevated serum CA 125 concentration. The cause of ascites and elevated tumor markers in hypothyroidism remains unknown. Diagnosis was characterized by no evidence of malignancy seen by transvaginal ultrasonography or abdominal computed tomography and ascites resolution with serum CA 125 normalization after adequate hormonal treatment. Our data suggest that hypothyroidism should be considered in patients with ascites and elevated serum CA 125.
Keywords: hypothyroidism; SAAG; tumor markers